Television with Stanley Cavell in Mind - LaRocca, David; Laugier, Sandra (TV-Philosophy, 2023)
This collection of new work on the philosophical importance of television starts from a model for reading films proposed by Stanley Cavell, whereby film in its entirety-actors and production included-brings its own intelligence to its realization. In turn, this intelligence educates us as viewers, leading us to recognize and appreciate our individual cinephilic tastes, and to know ourselves and each other better. This reading is even more valid for TV series. Yet, in spite of the progress of film-philosophy, there has been a paucity of concurrent analysis of the ethical stakes, the modes of expressiveness, and the moral education involved in television series. Perhaps most conspicuously, there has been a lack of focus on the experience of the viewer. Cavell highlighted popular cinema's capacity to create a common culture for millions. This power has become dispersed across other bodies of work and practices, most notably TV series, which have largely appropriated the responsibility of widening the perspectives of their publics, a role once associated with the silver screen. Just as Cavell's reading of films involved moral perfectionism in its intent, this project is also perfectionist, extending a similar aesthetic and ethical method to readings of the small screen. Because TV series are works that are public and thus shared, and often global in reach, they fulfil an educational role-whether intended or not-and one that enables viewers to anchor and appreciate the value of their everyday experiences. Contributions from: William Rothman, Martin Shuster, Elisabeth Bronfen, Hugo Clémot, David LaRocca, Jeroen Gerrits, Stephen Mulhall, Michelle Devereaux, Thibaut de Saint-Maurice, Hent de Vries, Catherine Wheatley, Byron Davies, Sandra Laugier, Paul Standish, Robert Sinnerbrink.